Classifying Cerebral Palsy: Are We Nearly There?. Issue 2 (March 2015) - Mandaleson, Avanthi; Lee, Yaozong; Kerr, Claire; Graham, H. Kerr
Abstract : Background: Cerebral palsy (CP) is the most common cause of physical disability in childhood in developed countries and encompasses a wide range of clinical phenotypes. Classification of CP according to movement disorder or topographical distribution is widely used. However, these classifications are not reliable nor do they accurately predict musculoskeletal pathology. More recently, the Gross Motor Function Classification System (GMFCS) has been introduced and its validity, reliability, and clinical utility have been confirmed. In 2005 it was suggested that children should be described and classified according to the GMFCS in all outcome studies involving children with CP, in the Journal of Pediatric Orthopaedics (JPO). This study aimed to describe utilization of the GMFCS in 3 journals: Journal of Bone and Joint Surgery (JBJS Am), JPO, and Developmental Medicine and Child Neurology (DMCN), over a 7-year period (2005 to 2011), and any relationship to the journal's impact factor. A secondary aim was to establish if differences in methodological quality existed between those studies utilizing GMFCS and those that did not. Methods: A targeted literature search of the 3 selected journals using the term "cerebral palsy" was conducted using the Medline database. Utilization of the GMFCS was assessed using report of these data in the methods or results section of the retrieved papers. The Methodological Index for Non-Randomized Studies (MINORS) was employed to evaluate the quality of papers published in JPO. Results: One hundred and fifty-four studies met the inclusion criteria and in 85 (68%) the GMFCS was used. Of these, 112 were published in JPO, of which 51 (46%) utilized the GMFCS, compared with 72% for JBJS Am, and 88% for DMCN. In the JPO, utilization of the GMFCS improved from 13% to 80%, over the 7-year study period. Conclusions: Utilization of the GMFCS has increased rapidly over the past 7 years in the JPO but there is room for further improvement. Level of Evidence: Not applicable.